Technological change and occupation mobility: A task-based approach to horizontal mismatch - Manuel Aepli (Global Labor Organization (GLO), 2019)
Technological change and its impacts on labour markets are a much-discussed topic in economics. Economists generally assume that new technology penetrating the labour market shifts firms' task demand. Given individuals' acquired and supplied skills, these task demand shifts potentially foster horizontal skill mismatches, e.g. individuals not working in their learned occupations. In this paper, I first analyse the relation between task shifting technological change and individuals' horizontal mismatch incidence. Second, I estimate individuals' mismatch wage penalties triggered by this relation. The present paper proposes an instrumental variable (IV) approach to map this mechanism and to obtain causal estimates on mismatch wage penalties. Applying this empirical strategy yields a wage penalty of roughly 12% for horizontally mismatched individuals.
Keywords: E24; J24; J62; O33; 330; horizontal mismatch; task-based approach; technological change; vocational education